IMPLEMENTASI STRATEGI DIGITAL MARKETING MELALUI MARKETPLACE SHOPEE DI SHAMARA HERBAL CIKARANG - Adiguna, Mochamad Adhari; Bambang Wisnu Widagdo; Muhammad Anis (KOMMAS: Jurnal Pengabdian Kepada Masyarakat, 2026)
Developments in the era of globalization have given rise to an increasingly rapid and dynamic digital era. Consequently, various stakeholders are required to adapt to this new environment of information technology, including business actors at small, medium, and large scales. By utilizing internet networks as a medium for conducting business, enterprises have significant opportunities to contribute to the global economic value chain. The adoption of digital media in entrepreneurial activities enables businesses to market their products more efficiently and to reduce operational costs, including the high costs associated with distribution. One of the major challenges faced by business actors in the digital economy era is the relatively low level of human resource capability in transitioning from conventional trading methods to digital-based commerce. Among these human resources are the participants of this activity, namely sales personnel, resellers, and marketers of Shamara Herbal Cikarang. Through this Community Service Program (Pengabdian kepada Masyarakat / PKM), the expected output is the development of training participants who understand and master the importance of digital marketing knowledge for entrepreneurship, enabling them to implement digital marketing strategies through the Shopee marketplace. This PKM activity was conducted on November 12, 2025, at Shamara Herbal Cikarang, Bekasi Regency, and involved lecturers and students from Universitas Pamulang, sales and marketing staff of Shamara Herbal, as well as resellers and marketers of Shamara Herbal Cikarang. The training participants consisted of store sales and marketing staff, along with resellers and marketers of Shamara Herbal Cikarang. As a result of this activity, the participants acquired the competence to implement digital marketing applications, particularly through the Shopee marketplace.